A randomized controlled trial of a multiple health behavior change intervention delivered to colorectal cancer survivors: Effects on sedentary behavior. Issue 17 (9th May 2014) - Lynch, Brigid M.; Courneya, Kerry S.; Sethi, Parneet; Patrao, Tania A.; Hawkes, Anna L.
<x xml:space="preserve">Abstract</x> BACKGROUND Sedentary behavior may independently contribute to morbidity and mortality among survivors of colorectal cancer. In the current study, the authors assessed whether a telephone‐delivered multiple health behavior change intervention had an effect on the sedentary behavior of recently diagnosed colorectal cancer survivors. METHODS A total of 410 participants were recruited through the Queensland Cancer Registry and randomized to the health coaching (intervention) or usual‐care (control) group. Eleven health coaching sessions addressing multiple health behaviors, including sedentary behavior, were delivered over a period of 6 months. Data were collected at baseline (before randomization), at 6 months, and at 12 months via a telephone interview. RESULTS At 12 months, there was a significant decrease noted in the hours per day of sedentary time in both the health coaching (−1.21; 95% confidence interval [95% CI], −1.71 to −0.70) and usual‐care groups (−0.55; 95% CI, −1.06 to −0.05), but the between‐group difference was not found to be statistically significant (−0.65; 95% CI, −1.37 to 0.06 [P = .07]). In stratified subgroup analyses, the multiple health behavior change intervention was found to have a significant effect on total sedentary time (hours/day) at 12 months in survivors of colorectal cancer who were aged > 60 years (−0.90; 95% CI, −1.80 to −0.01 [P = .05]), male (−1.33; 95% CI, −2.44 to −0.21 [P = .02]), and nonobese (−1.10; 95% CI, −1.96 to −0.25; [P = .01]). CONCLUSIONS Incorporating simple messages about limiting sedentary behaviors into a multiple health behavior change intervention was found to have modest effects on sedentary behavior. A sedentary behavior‐specific intervention strategy may be required to achieve substantial changes in sedentary behavior among colorectal cancer survivors. Cancer 2014;120:2665–2672. © 2014 American Cancer Society.